Macroeconomic Indicators and Sukuk Market Performance in Selected OIC Economies : english - Nursilah Ahmad; Asma Abdul Rahman; Syazwani Abdul Rahim; Nurul Atika Azzan (Tazkia Islamic Finance and Business Review, 2021)
Sukuk plays a critical role in developing Islamic finance globally. Therefore, it is important to identify macroeconomic determinants that drive the sukuk market. The study investigates the relationship between macroeconomic indicators and sukuk market performance for the period 2004 until 2019 in 10 sukuk issuing countries using a panel data approach. The macroeconomic indicators are Gross Domestic Product (GDP), consumer price index, trade openness, exchange rates, and financial crisis. The findings reveal that GDP, trade openness, and exchange rates have a significant impact on sukuk market performance. In addition, the study analyses the growth components of GDP in these countries five years before the Covid-19 pandemic outbreak. The countries' performance in terms of changes in percentage contribution of consumption, investment, government spending, and net export, towards GDP growth, is measured. The findings indicate that the consumption component contributes the most to economic stability. Therefore, the authorities can implement policies that would support productive consumption and design trade policies that will enhance sukuk market performance. Keywords: Sukuk, Macroeconomic Indicators, Islamic Bond, GDP Decomposition